Utilização da prototipagem 3D para treinamento de técnicas radiográficas odontológicas - Giacomini, Giuliano Omizzolo (2019)
The aim of this article is to present a 3D printed model developed for the training of intraoral radiographic techniques. A skull STL file was manipulated in segmentation software (Meshmixer and Netfabb) and printed by FDM (fused deposition modelling) technology. The prototype skull bones were printed separately, using PLA (polylactic acid) filament, and joined by heating and bonding. The mandible was printed using flexible filament and articulated to the skull by attaching the mandibular condyle to the articular fossa of the temporal bone with a spring and a metal screw. The protype intra-oral radiographs were performed with a digital sensor (RVG 5100, Carestream). The total cost for prototype printing was $ 34.00. The PLA filament presented a satisfactory radiographic image to allow the geometric representation. Some anatomical structures, such as the periodontal ligament space, the zygomatic process of the maxilla and the intermaxillary suture, could be radiographically represented. The use of 3D printing to manufacture models that adjuvant in the teaching-learning process of intraoral radiographic techniques is presented as an alternative to commercial manikins, combining radiographic projection quality and affordable cost.